Prevalencia de mycoplasma hyopneumoniae en porcinos de traspatio en el cantón Salcedo, provincia de Cotopaxi. - Cunalata Pinto, Santiago David (2023)
In Ecuador, backyard pigs production is based on Creole breed, and there is a large part of the community that owns this type of pig, where Creole breed predominates because they are much more resistant to existing conditions in the production system, but they are not well managed, they are susceptible to contracting different diseases such as M. hyopneumoniae. The objective of this research was to identify positive cases of M. hyopneumoniae in backyard pigs in Salcedo canton, Cotopaxi province, using competitive ELISA test. First, samples were collected from 150 animals to obtain serum. Subsequently, the ELISA test was performed with obtained serum to identify positive cases. In order to perform statistical analyses such as dynamic tables in Excel to determine prevalence, R program to obtain the chi-square, was used to identify correlation between age and sex variables with positive cases. From the data obtained, 12 positive cases were positive for M. hyopneumoniae, representing a prevalence of 8%. Regarding sex variable, there were 8 positive cases in females and 4 in males, which means p value (0.8160) it was identified that there is no correlation based on the sex variable with the M. hyopneumoniae presence. As for the variable age, there were 8 positive cases in the group younger or equal to 6 months, 4 positive cases in the group older than 6 or equal to 12 and 0 positive cases in the group older than 12, which based on p-value obtained (0.5571) it was possible to identify no correlation with respect to age with positive cases. Based on epidemiological map, it was possible to identify a higher prevalence of disease in Mulliquindil parish, which could be related to the animals management in this sector.